Antibiotic optimization in hospitalized children with non-severe community-acquired pneumonia: lessons from an antimicrobial stewardship intervention (2022–2024) - Attaianese, Federica; Privato, Roberto; Montagnani, Carlotta; Stivala, Micol; Trapani, Sandra; Galli, Luisa; Indolfi, Giuseppe (Frontiers in Pediatrics, 2025)
Background and objectivesCommunity-acquired pneumonia (CAP) is a leading cause of hospitalization and antibiotic use in children. Despite guidelines recommending narrow-spectrum regimens and shorter treatment durations, prescribing practices remain inconsistent. This study assessed the impact of a newly implemented diagnostic and therapeutic clinical pathway (CP) as part of an antimicrobial stewardship (AMS) intervention in a tertiary care pediatric hospital.MethodsA single-center, retrospective observational study was conducted on children aged 28 days to 18 years hospitalized with non-severe, uncomplicated CAP from January 2022 to December 2024. The CP was implemented on January 1st, 2024. Antibiotic prescribing patterns, clinical outcomes, and predictors of short-course therapy (≤5 days) were compared between pre- and post-CP periods. Multivariate logistic regression identified predictors of intravenous (IV) therapy ≤48 h, total therapy ≤5 days, and ampicillin use as first-line agent.ResultsThe study included 263 CAP episodes in 250 children. Following the implementation of CP, the use of ampicillin as a first-line IV antibiotic significantly increased [19/99 (19%) vs. 1/164 (0.6%); p < 0.001]. A higher proportion of post-CP patients received IV antibiotics for ≤48 h [25/99 (25%) vs. 20/164 (12%); p = 0.006], reflecting an increased rate of early IV-to-oral switch. However, total antibiotic duration and hospital length of stay (LOS) remained unchanged. Viral detection in respiratory samples predicted antibiotic courses of ≤5 days.ConclusionsCP implementation improved adherence to evidence-based antibiotic prescribing, reduced broad-spectrum use, and increased early IV-to-oral transitions without compromising outcomes. However, unchanged therapy duration and LOS highlight the need for further AMS interventions, clinician education, and integration of viral and bacterial diagnostics to support optimal antibiotic use.